Pengaruh Tanaman Refugia Kenikir (Cosmos caudatus) dan Marigold (Tagetes erecta L.) terhadap Serangan Lalat Buah (Bactrocera spp.) pada Tanaman Cabai Merah Besar (Capsicum annuum L.) di Lahan Gambut - Feri Arianto; Salamiah Salamiah; Samharinto Soedijo (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Big red chili (Capsicum annuum L.) is a commodity that is very much needed, especially in the food industry and its needs are often increasing. The increasing demand is inversely proportional to the availability of chili that cannot be fulfilled. The causes include the constraints of fruit fly (Bactrocera spp.) attacks that always occur on chili plants. Symptoms caused by the presence of small holes in the chili fruit, the fruit falls out and there are larvae in the fruit. Control that is often done is to use chemical insecticides which can cause environmental pollution. One solution is to use refugia plants. This study was conducted to determine the effect of refugia plants on fruit fly attacks on chili plants and the effectiveness of kenikir (Cosmos caudatus) and marigold (Tagetes erecta L.) plants in suppressing fruit fly attacks on chili plants. The design used was a randomized block design (RAK) with 4 treatments, control (T0), kenikir and marigold plants planted with chili (T1), kenikir plants planted with chili (T2), marigold plants planted with chili (T3) and repeated as many as six times. The results of observations, refugia plants affect fruit fly attacks. Refugia marigold plant, the intensity of attack of fruit flies reached 6.01% and 19.30%, while the intensity of attack of kenikir was 13.61% and 33.61%, respectively